Towards a Simulator for Green Smart Campus Systems - Moraes, Priscila; Pisani, Flávia; Borin, Juliana (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2020)
The 2030 Agenda for Sustainable Development aims to foster environmental protection, inclusive economic growth, and social inclusion. Universities are called to join this global effort and are expected not only to contribute with solutions for the sustainability challenges but also provide sustainable campi. Given this scenario, the main contributions of this paper are threefold: i) to illustrate how universities could contribute with the 2030 Agenda through smart campus solutions based on technologies such as Internet of Things, Big Data, and Cloud Computing; ii) to propose a framework to automatically collect data to generate and manage sustainability indicators in the university; and iii) to propose a simulator for green smart campus system which allows an adequate estimate of the required information and communication infrastructure.